ijps 2021
DOI: 10.36468/pharmaceutical-sciences.spl.340
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Evaluation of Gastric Cancer Risk Prediction Model

Abstract: To predict the probability of gastric cancer and precancerous lesions in patients and construct a risk model for gastric cancer based on related risk factors. 189 patients with gastric cancer or precancerous lesions diagnosed by pathological examination in our hospital from October 2016 to May 2021 were selected as the experimental group and 203 patients with chronic gastritis during the same period as the control group. Collect the clinical data of the two groups of patients use single factor analysis to scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…Similar findings were reported in the few earlier studies that assessed the benefit of adding sodium hyaluronate to the treatment regimen of DED after cataract surgery. 14 , 16 , 23 Chen et al 14 observed that sodium hyaluronate was able to restore the structure of the tear film and improve the regularity of the corneal surface. In agreement with our study, Lu et al 16 found that combining sodium hyaluronate with pranoprofen, tobramycin, and dexamethasone improved the curative effect compared to when sodium hyaluronate was lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were reported in the few earlier studies that assessed the benefit of adding sodium hyaluronate to the treatment regimen of DED after cataract surgery. 14 , 16 , 23 Chen et al 14 observed that sodium hyaluronate was able to restore the structure of the tear film and improve the regularity of the corneal surface. In agreement with our study, Lu et al 16 found that combining sodium hyaluronate with pranoprofen, tobramycin, and dexamethasone improved the curative effect compared to when sodium hyaluronate was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our study, Lu et al 16 found that combining sodium hyaluronate with pranoprofen, tobramycin, and dexamethasone improved the curative effect compared to when sodium hyaluronate was lacking. Yang and Wang 23 reported that sodium hyaluronate combined with pranoprofen had effectively treated DED and was able to enhance tear secretion, keep ocular moisture, recover tear film stability, and improve the patients’ quality of life. Moreover, Duan and Tang 24 investigated the clinical efficacy of sodium hyaluronate, compound dextran, and polyethylene glycol eye drops in the treatment of DED after cataract surgery and found that sodium hyaluronate outperformed the two other medications.…”
Section: Discussionmentioning
confidence: 99%
“…Similar ndings were reported in the few earlier studies that assessed the bene t of adding sodium hyaluronate to the treatment regimen of DED after cataract surgery. 13,15,22 Chen et al 13 observed that sodium hyaluronate was able to restore the structure of the tear lm and improve the regularity of the corneal surface. In agreement with our study, Lu et al 15 found that combining sodium hyaluronate with pranoprofen, tobramycin, and dexamethasone improved the curative effect compared to when sodium hyaluronate was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our study, Lu et al 15 found that combining sodium hyaluronate with pranoprofen, tobramycin, and dexamethasone improved the curative effect compared to when sodium hyaluronate was lacking. Yang and Wang 22 reported that sodium hyaluronate combined with pranoprofen had effectively treated DED and was able to enhance tear secretion, keep ocular moisture, recover tear lm stability, and improve the patients' quality of life. Moreover, Duan and Tang 23 investigated the clinical e cacy of sodium hyaluronate, compound dextran, and polyethylene glycol eye drops in the treatment of DED after cataract surgery and found that sodium hyaluronate outperformed the two other medications.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that population-based mass screening and the eradication of Hp should be considered to reduce the burden of GC in high-risk settings. Moreover, Yang, Y (2021) [18] conducted single-factor analysis of Hp infection, which showed the groups of patients with GC and precancerous lesions were significantly higher than those in the control group. Multi-factor logistic regression analysis verified that Hp infection was an independent risk factor for GC, which could provide a data reference for early GC, and the GC risk model constructed on this basis had a good fitting (AUC = 0.924).…”
Section: Clinical Indicatorsmentioning
confidence: 99%